ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) FACTORS IN FINANCIAL MANAGEMENT: A SYSTEMATIC REVIEW AND RESEARCH AGENDA - Gunawan Widjaja (CV. Adiba Aisha Amira, 2024)
Environmental, Social, and Governance (ESG) factors play an increasingly important role in contemporary financial management. The integration of ESG into business strategy and financial decision-making not only reflects a company's responsibility to society and the environment, but also contributes to improved long-term financial performance. Companies that implement strong ESG practices tend to demonstrate better risk management, a stronger reputation, and greater appeal to responsible investors. In addition, a focus on ESG helps companies identify innovation opportunities, improve operational efficiency, and meet increasing stakeholder expectations. As such, ESG has become an integral component of modern financial management, influencing aspects ranging from capital allocation and investment appraisal to financial reporting and long-term growth strategies. In conclusion, this review confirms the importance of ESG factors in modern financial management and highlights its potential as an effective business strategy to achieve long-term financial success in a business environment that increasingly emphasises sustainability and social responsibility.